DRUG UTILIZATION ANALYSIS OF ANTI-SNAKE VENOM AT A TERTIARY CARE CENTER IN CENTRAL MAHARASHTRA: A 3-YEAR RETROSPECTIVE STUDY - Asawale, Ketan Y; Mehta, Mukesh C; Uike, Pravin S (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: In India, snakebite is a major public health problem. Anti-snake venom serum (ASVS) is the definitive treatment for poisonous snakebites. However, the non-availability of effective ASVS to treat the specific types of snakebite envenomation encountered in various regions of the world has become a critical health issue at global level. In the present observational descriptive study, we observed the prescribing pattern and rationality of ASVS and the dosage of ASVS at our hospital and compared them with the standard guidelines in the treatment of snakebite cases with the aim to observe optimum utilization of ASVS. Methods: Data collection of registered cases of snakebite of 3 years from January to December 2012, 2013, and 2014 was carried out between January 2015 and December 2015. Results: A total of 935 cases were studied. ASVS treatment was given to 774 cases of snakebite, out of which 161 had no bite marks and 613 patients had bite marks. Majority (615 [79.45%]) of cases were treated with 1–20 vials of ASVS during total stay at center. Overall, 899 cases were discharged, among them 606 cases were not followed the World Health Organization guidelines. 29 cases succumbed and seven were referred to other center. The mortality observed during the 3 years was 3.10%. Conclusion: We observed individualized treatment for treatment with ASVS, thereby reducing the use of ASVS. Thus, we conclude that individualized approach depending on locally predominant snakes for the treatment of snakebite based on the degree of envenomation is a way by which the scarce ASVS can be used optimally.